CORRELATION TRIGLISERIDA LEVEL AND MONOCYTE IN CORONARY HEART DISEASE AT ULIN GENERAL HOSPITAL BANJARMASIN - Juwita, Gusti Adistya Naila; Arifin, Miftahul; Yuliana, Ida (Berkala Kedokteran, 2017)
Abstract: Coronary heart disease (CHD) is an unbalance condition between oxygen supply and demand in heart muscle which caused by coronary artery obstruction known as atherosclerosis. Both triglyceride and monocyte have important role in the process of atherosclerosis plaque forming which cause CHD. This research aimed to analyse correlation between triglyceride level and monocyte count in patients with coronary heart disease at Ulin General Hospital Banjarmasin on August 2014-August 2015. This research is an analytical observational research with cross-sectional approach. Total sample for this research are 94 CHD patients selected by inclusion criteria. The result discovered the average rate for triglyceride level is 114 mg/dL and for monocyte count is 0,62 thousand/ÂµL. Based on result of data analysis with Pearson correlation test demonstrates the value of r=0,347 and p=0,01. It can be concluded that there is weak, significant and positive correlation between triglyceride level and monocyte count in CHD patientsÂ Keywords: triglyceride, monocyte, coronary heart disease